REVISITING TATAYYUR: A DIALOGUE BETWEEN TRADITION AND CONTEXT IN TAFSIR AL-MISHBAH THROUGH GADAMER’S HERMENEUTICS - Mar’atul Insanissa’adah; Ahmad Zuhri; Mardian Idris Harahap (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
This study examines the concept of tatayyur in the Qur’an as interpreted by M. Quraish Shihab in Tafsir al-Mishbah, employing Hans-Georg Gadamer’s hermeneutics as the analytical framework. The Qur’an rejects tatayyur as a fatalistic belief that undermines human agency and emphasizes individual moral responsibility. Through Tafsir al-Mishbah, Shihab expands the meaning of tatayyur by highlighting its social, psychological, and cultural dimensions, thereby addressing the real challenges faced by Indonesian Muslims who remain influenced by superstitious practices. By applying Gadamer’s concepts of productive prejudice, effective history, and fusion of horizons, this research finds that Shihab’s interpretation emerges from a dynamic encounter between classical exegetical tradition and the contextual needs of modern Indonesia. The findings demonstrate that Gadamerian hermeneutics provides a productive methodological approach to Qur’anic exegesis, as it enables an ongoing dialogue between the sacred text and contemporary social realities. This research affirms that a hermeneutic and contextual reading strengthens the Qur’an’s message of rejecting superstition, fostering optimism, and reinforcing moral responsibility in Muslim society.